A Review on the Sex Differences in Organ and System Pathology with Alcohol Drinking - Vatsalya, Vatsalya; Bin Liaquat, Hammad; Ghosh, Kuldeep; Prakash Mokshagundam, Sri; J McClain, Craig (Current Drug Abuse Reviews, 2016)
Hazardous consequences of alcohol consumption adversely influence overall health, specifically physical and mental health. Differences in alcohol consumption and manifestations in pathology have been observed between males and females, however research on understanding these differences is limited. Negative consequences of alcohol consumption have now been studied including sex as a significant factor. Some studies have shown differences in the severity of consequences of alcohol consumption between the sexes, both in the mental consequences and changes/ injury in various organ systems. Over time, reports in females on both the dynamics of drinking and on the hazardous consequences of alcohol consumption have grown, primarily because of more awareness, better observation, and the inclusion of sex as a factor in scientific investigations. This paper reviews role of sex differences in pathophysiological and behavioral consequences of alcohol drinking.
Keywords: sex difference